2014
DOI: 10.1371/journal.pone.0089096
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Bisphenol A Exposure Impacts the Fetal Heart Transcriptome

Abstract: Conditions during fetal development influence health and disease in adulthood, especially during critical windows of organogenesis. Fetal exposure to the endocrine disrupting chemical, bisphenol A (BPA) affects the development of multiple organ systems in rodents and monkeys. However, effects of BPA exposure on cardiac development have not been assessed. With evidence that maternal BPA is transplacentally delivered to the developing fetus, it becomes imperative to examine the physiological consequences of gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 72 publications
1
36
0
1
Order By: Relevance
“…However, unconjugated BPA levels in pregnant rhesus monkeys (vom Saal et al, 2014) that were within the range reported in numerous human biomonitoring studies (Vandenberg et al, 2007, 2010a) were reported to have adverse effects in a series of studies examining fetal tissues (ovary, mammary gland, brain, lung, uterus and heart) from the female fetuses carried by pregnant rhesus monkeys (Calhoun et al, 2014; Chapalamadugu et al, 2014; Elsworth et al, 2013; Hunt et al, 2012; Tharp et al, 2012; Van Winkle et al, 2013). The monkey fetus findings for ovary, mammary gland and brain recapitulate previously reported effects from numerous studies in rodents (reviewed in Vandenberg et al, 2013a).…”
Section: Extensive Bpa Hazard Data Dispute the Assumption That Biomentioning
confidence: 75%
“…However, unconjugated BPA levels in pregnant rhesus monkeys (vom Saal et al, 2014) that were within the range reported in numerous human biomonitoring studies (Vandenberg et al, 2007, 2010a) were reported to have adverse effects in a series of studies examining fetal tissues (ovary, mammary gland, brain, lung, uterus and heart) from the female fetuses carried by pregnant rhesus monkeys (Calhoun et al, 2014; Chapalamadugu et al, 2014; Elsworth et al, 2013; Hunt et al, 2012; Tharp et al, 2012; Van Winkle et al, 2013). The monkey fetus findings for ovary, mammary gland and brain recapitulate previously reported effects from numerous studies in rodents (reviewed in Vandenberg et al, 2013a).…”
Section: Extensive Bpa Hazard Data Dispute the Assumption That Biomentioning
confidence: 75%
“…Another study reported that feeding BPA to pregnant rhesus monkey resulted in change of the transcriptome of fetal heart, suggesting that structural change of heart could happen because of chronic prenatal BPA exposure. 38 Additionally, we had reported an association between BPA exposure and decreased heart rate variability in the elderly, suggesting BPA's action on the autonomic nervous system, which regulates cardiovascular function. 7 The increase of children's BP in the present study may be explained by these mechanisms; however, the specific molecular and cellular mechanisms behind the effect of prenatal BPA exposure on BP are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 98%
“…Otro estudio comunicó que incorporar BPA en la alimentación del mono rhesus determinaba un cambio del transcriptoma del corazón fetal, lo que sugirió que podría haber cambio estructural del corazón debido a la exposición prenatal crónica a BPA. 38 Además, habíamos comunicado una asociación entre exposición a BPA y menor variabilidad de la frecuencia cardíaca en ancianos, lo que sugería la acción del BPA sobre el sistema nervioso autó-nomo, que regula la función vascular. 7 En el presente estudio, el aumento de la PA de los niños se puede explicar por estos mecanismos; sin embargo, aún se deben dilucidar los mecanismos moleculares y celulares específicos responsables del Tabla 2.…”
Section: Discussionunclassified
“…Although baseline expression levels of Myh6 during murine cardiogenesis do not show a discernible difference between the left and right ventricle, 46 it is interesting to note that bisphenol A, an ubiquitous environmental chemical, has been shown to selectively downregulate MYH6 expression by ≈42-fold in the left ventricle of the fetal heart. 47 Similarly, the age-dependent development of right ventricular systolic dysfunction may be multifactorial, attributable to biallelic MYH6 mutations in the context of a vulnerable systemic morphological right ventricle 48 exposed to volume and pressure overload, hypoxemia, and recurrent cardiopulmonary bypass. Of the 4 MYH6 mutations identified, the maternally inherited mutations were located in the head domain and predicted to impair power stroke recovery (I704N) or its interaction with actin (D588A).…”
Section: Recessive Myh6 Mutations In Hlh With Reduced Ejection Fractionmentioning
confidence: 99%